Influence of Spark Plasma Sintering (SPS) Conditions on Transmission of MgAl2O4 Spinel. Issue 2 (6th November 2014) - Morita, Koji; Kim, Byung‐Nam; Yoshida, Hidehiro; Hiraga, Keijiro; Sakka, Yoshio; Reimanis, I.
<x xml:space="preserve">Abstract</x> The effects of the spark plasma sintering (SPS) parameters, such as heating rate α, temperature T and soak time ts, and impurities on in‐line transmission Tin were examined in MgAl2O4 spinel. The SPS processing at T = 1300°C for ts = 20 min with a low heating rate of α = 10°C/min is a preferable condition for attaining higher Tin. For the higher T or the longer ts, grain coarsening enhanced the coalescence of residual pores and second phase precipitation, resulting to the limited Tin even at the slow α. Although the lower T and longer ts attained fine and dense microstructure simultaneously, the maximum Tin was limited to about 50%. The limited transmission, particularly in the visible range, can be ascribed to the discoloration caused by the carbon contamination. The carbon contamination arose from the preexisting trace CO3 impurities, irrespective of the SPS conditions. For the higher α, which is the primary advantage of the SPS technique, the additional carbon contamination occurred from the paper/die and remained as glassy carbon in the matrix. To attain higher Tin by the SPS technique, the lower α and T, and the shorter ts should be utilized after removing the impurities.